2006
DOI: 10.1073/pnas.0510834103
|View full text |Cite
|
Sign up to set email alerts
|

MAGE-A tumor antigens target p53 transactivation function through histone deacetylase recruitment and confer resistance to chemotherapeutic agents

Abstract: The MAGE gene family is characterized by a conserved domain (MAGE Homology Domain). A subset of highly homologous MAGE genes (group A; MAGE-A) belong to the chromosome X-clustered cancer͞testis antigens. MAGE-A genes are normally expressed in the human germ line and overexpressed in various tumor types; however, their biological function is largely unknown. Here we present evidence indicating that MageA2 protein, belonging to the MAGE-A subfamily, confers wild-type-p53-sensitive resistance to etoposide (ET) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
219
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(235 citation statements)
references
References 38 publications
12
219
2
2
Order By: Relevance
“…25 We have previously demonstrated that upon DNA damage MageA2 expression hampers the apoptotic response of cells by affecting p53 acetylation and transactivation function. 10 PMLIV is a known regulator of p53; indeed it has been shown that PMLIV by recruiting p53 to PML-NBs facilitates its acetylation inducing its transcriptional activity. 18,21 In this context, we asked whether MageA2 could also affect p53 acetylation as induced by PMLIV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 We have previously demonstrated that upon DNA damage MageA2 expression hampers the apoptotic response of cells by affecting p53 acetylation and transactivation function. 10 PMLIV is a known regulator of p53; indeed it has been shown that PMLIV by recruiting p53 to PML-NBs facilitates its acetylation inducing its transcriptional activity. 18,21 In this context, we asked whether MageA2 could also affect p53 acetylation as induced by PMLIV.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in human primary melanoma cells, MageA2 expression confers resistance to chemotherapeutic drugs by interfering with p53 acetylation, which can be reverted by HDAC inhibitor drugs. 10 Subsequently, other groups also described an opposite correlation between MAGE-A gene expression and p53 activity. 7,11,12 Interestingly, only MageA4 has been shown to be involved in some potentially anti-tumor functions such as gankyrin oncoprotein inhibition 13 and apoptosis induction.…”
mentioning
confidence: 99%
“…These effects were thought to be mediated by regulation of p21 gene (Wilson et al, 2006). At a mechanistic level, HDAC3 was shown to be recruited by the tumor antigen MAGE-A to impair the transactivation of the tumor suppressor p53, thereby conferring chemoresistance (Monte et al, 2006). Finally, Narita et al (2005), based on studies with human maxillary carcinoma cells, proposed that inhibition of HDAC3 combined with hyperthermia may provide an efficient therapeutic approach for cancer.…”
Section: Hdac3 and Cancermentioning
confidence: 99%
“…Des études supplémentaires ont montré que cette résistance à l'apoptose était associée à une action neutralisante des MAGE sur P53 [16]. En accord avec ces données, une autre étude a montré que MAGE-A2, un membre de la même famille, recrute l'histone-déacé-tylase 3 (HDAC3) et cible P53, et s'oppose ainsi à l'acétylation et à l'activation de P53 à la suite d'un traitement génotoxique [17]. De plus, MAGE-A1 recrute l'histone désacétylase HDAC1 et ainsi transforme le régulateur transcriptionnel SKIP en un répresseur de transcription [18].…”
Section: Le Rôle De Borisunclassified